Islamic Perspective on Organizational Citizenship Behavior Among Academic Staff in Indonesian State Islamic Higher Education: Is It Effective? - Shohib, Muhammad Wildan; Azani, Mohammad Zakki; Dartim, Dartim; Nubail, Ahmad; Inayati, Nurul Latifatul (Universitas Muhammadiyah Surakarta, 2024)
This study examines the perceived level of organizational citizenship behavior based on Islamic perspective (OCBIP) practices among academic staff in the Indonesian States' Islamic Higher Education Institutions (ISIHEIs). This study also sought to observe differences in the perceived level of OCBIP among academic staff by gender. A quantitative survey method was employed to collect the data from 450 academic staff of six State Islamic Higher Education Institutions (ISIHEIs) across Indonesia using a five-point OCBIP scale. Descriptive statistics, independent-sample t-tests, and bivariate correlations between antecedents of OCBIP were carried out with SPSS software version 25. The analysis of the study exhibits the perceived level of OCBIP practices among academic staff and gender influences on the perceived variables. The hypothesized model of the study added a new theory and knowledge of OCBIP from the Indonesian State Islamic Higher Education Institutions context that can be used to improve organizational effectiveness in ISIHEIs. The study's findings suggest that the value of the OCBIP practices by academic staff can boost the effectiveness of higher education institutions. The study tested, examined, and formulated OCBIP practices for ISIHEIs. The findings also contribute to understanding how OCBIP could be used to develop organizational effectiveness in the context of ISIHEIs.